The Unique Periodic Solution of Abel’s Differential Equation - Ni Hua (Journal of Mathematics)
In this paper, the existence of a periodic solution for Abel’s differential equation is obtained first by using the fixed-point theorem. Then, by constructing the Lyapunov function, the uniqueness and stability of the periodic solution of the equation are obtained.